Affective Priming by Simple Geometric Shapes: Evidence from Event-related Brain Potentials - Wang, Yinan; Zhang, Qin (Frontiers in Psychology, 2016)
Previous work has demonstrated that simple geometric shapes may convey emotional meaning using various experimental paradigms. However, whether affective meaning of simple geometric shapes can be automatically activated and influence the evaluations of subsequent stimulus is still unclear. Thus the present study employed an affective priming paradigm to investigate whether and how two geometric shapes (circle vs. downward triangle) impact on the affective processing of subsequently presented faces (Experiment 1) and words (Experiment 2). At behavioral level, no significant effect of affective congruency was found. However, ERP results in Experiment 1 and 2 showed a typical effect of affective congruency. The LPP elicited by affective incongruent trials was larger compared to congruent trials. Our results provide support for the notion that downward triangle is perceived as negative and circle as positive and their emotional meaning can be activated automatically and then exert an influence on the participants’ evaluation at electrophysiological level. In addition, the lack of significant congruent effect in behavioral measures and the inversed N400 congruent effect might reveal that the affective meaning of geometric shapes is weak because they are just abstract threatening cues rather than real threat.